The Application Of Blended Learning Model To Increase The Students Learning Achievement On Qur'an Hadits Subject Of Mts Qur'aniah Musi Rawas - Muhtadi, Muhtadi; Helandri, Joni; Arikarani, Yesi (Edification Journal : Pendidikan Agama Islam, 2022)
The development of the world of education is increasing marked by changes in learning with sophisticated technology or another term called the industrial revolution 5.0, one of which is the use of educational technology. With a background in the changing pattern of teaching and learning during a pandemic with the familiar use of blended learning models or combining online and offline learning. However, with the model used, several problems arise, namely not being able to understand the material presented properly, the learning model used by the teacher has not been able to motivate students in learning. Have not used learning media that can make it easier for students to understand the subject matter presented by the teacher. With this problem, it will be discussed using the classroom action research method with the stages of action research in a cycle including planning or carrying out observations and reflections. Based on the results of descriptive and qualitative quantitative data analysis, the application of the Blended Learning model can improve the learning outcomes of Al-Qur'an Hadith subjects for class VIII MTs Qur'aniah, Musi Rawas Regency first, first, pre-cycle test results, the highest score is 80 and the lowest score is 60. , while the test results in the second cycle the highest score was 100 and the lowest score was 70. Second, the average grade based on the pre-cycle test results was 67.42, while in Cycle II the test results increased to 88.55. Third, students who finished studying from 29.03% pre-cycle and at the end of the second cycle in this study the students who scored according to the KKM increased to 93.55%.